Directors' view on exemption from statutory audit - Othman, Rohana; Zainal Abidin, Zubaidah; Thirumanickam, Nagerathnam; Kaur, Jagjit (2011)
Fundamentally, an audit is important to inform shareholders about the well being of the company's finances. An audit helps the shareholders as well as stakeholders to make informed decisions based on how the company is performing. In recent years, the issue of audit exemption among small companies has been addressed in many studies in the United Kingdom, Australia and Singapore. Over the years, these countries and several others have exempted small companies from the annual audit requirement. Malaysia still legally obligates all her companies, irrespective of their size, to undergo annual audit. This study explores factors that may be associated with the take-up level of audit exemption among SMEs in Malaysia namely; value of audit, financing strategy, future plans, size of firms, director's qualification, dependent users and audit cost. Results indicate that all six factors have a significant relationship with the take-up level of audit exemption with the exception of director's qualification. The majority of SMEs in this study chose to continue with statutory audit even if they are not legally required to do so, showing that there is a low take-up level of audit exemption among SMEs. The results from this study provide useful information for policy makers, auditors and directors of small companies.